Tradwomen of America: White, Angry and Feeling Betrayed - Annus, Irén (AMERICANA E-journal of American Studies in Hungary, 2019)
At the dawn of this century, the sheer shock of 9/11 stirred up a series of fierce debates in the US about traditional hegemonic masculinity. Proposing that the event symbolized American men’s failure to protect the nation, some argued for a search for possible avenues for healing and a reconstruction of American masculinity. The housing crisis of 2008, however, along with the subsequent economic recession and the election of the first non-white American president have been interpreted by some as further signs of traditional American manhood in crisis. Masculinity Studies scholar Michael Kimmel has investigated the history of hegemonic masculinity in the US and mapped the reasons behind the recent mounting sense of anger among a growing population of men, which ultimately played a crucial role in the election of Donald Trump as president. In parallel, various studies have also focused on an increasing anger among American women, triggered in part by the patriarchal social order and racist tendencies still prevailing in American society, which has given birth to movements such as #MeToo, #BlackLivesMatter and #SayHerName. However, little has been written about the anger and frustration among more traditional women who have been supporting Trump alongside their brothers, sons and husbands. The study takes a closer look at this, often invisible group of tradwomen and investigates the contexts and factors that have fueled their anger and driven them to continue to be devoted Trump believers, activists, alt-right ideologues or members of white supremacist groups.